EFEKTIVITAS PELAKSANAAN PROGRAM ADVOKASI KEBIJAKAN STUNTING DI DINAS P3AP2KB KABUPATEN PASURUAN - Aminullah; Riris Setiyo Rini (Halu Oleo University, 2023)
Stunting is a national priority issue that is now being intensively addressed to prevent the risk of stunting and reduce the stunting rate in Indonesia. In this case, children who experience stunting greatly impact the quality of the nation's generation because it can result in low intellectual levels and productivity. This study uses a qualitative approach, namely the resulting data is in the form of a description and critical analysis of an incident observed in the field. The location of this research was at the Office of Women's Empowerment, Child Protection, Population Control, and Family Planning(P3AP2KB) in Pasuruan Regency. In this study, the data analysis techniques used were observation, interviews, and documentation. Based on the findings in the field, in addition to the high dispensation for marriage in the religious courts, Pasuruan Regency also received the third rank of marriage constituencies. This finding will provide an assessment of stunting policy advocacy at the maturing marriage age, which is considered not optimal and effective. The purpose of this study is to analyze the effectiveness of the stunting policy advocacy program, one of which is maturing the age of marriage, and the obstacles to implementing the program for maturing the age of marriage.